THE TRAVELLING SALESMAN PROBLEM IN THE ENGINEERING EDUCATION PROGRAMMING CURRICULUM - Gayev, Yevgeny; Kalmikov, Vadim (Proceedings of National Aviation University (archive), 2017)
Objective: To make students familiar with the famous Traveling Salesman Problem (TSP) and suggest the latter to become a common exercise in engineering programming curriculum provided the students master computer science in the easy programming environment MATLAB. Methods: easy programming in MATLAB makes true such modern educational approach as “discovery based” methodology. Results: a MATLAB TSP-program oriented to Ukrainian map is suggested that allows to pictorially demonstrate the process of optimal route search with an option to decelerate or accelerate the demonstration. The program is guessed to be useful both for learning the TSP as one of fundamental logistics problems and as an intriguing programming curriculum excersize. Several sub-programs according to key stone Computer Science Curriculum have also been suggested. This lies in line with recent “discovery based” learning methodology. Discussion: we explain how to create this program for visual discrete optimization, suggest required subprograms belonging to key stone programming algorithms including rather modern graphical user interface (GUI), how to use this MATLAB TSP-program for demonstration the drastical grows of solution time required. Conclusions: easy programming being realized in MATLAB makes dificult curriculum problems attractive to students; it focuses them to main problem’ features, laws and algorithms implementing the “discovery based” methodology in such a way.